Answers

2014-11-15T22:32:37+08:00
x=-1         x3 + 4x2 + kx - 5
        -1]    1       4       k   -5
             +          a      c   e
               *1       b       d   f        *bring down

steps:
a= -1(value of x) multiply it by *1     (-1x1)      => -1        -1]   1   4    k   -5
b= 4 plus a                                    (4+-1)      => 3             +    -1   -3    5
c= -1(value of x) multiply it by b      (-1x3)      => -3               1   3   -5    0
f= 0 since the equation has no remainder       => 0
e= f or 0 minus -5                          (0+5)       => 5
d= e divided by -1(value of x)          (5/-1)      =>-5
k= d minus c                                 (-5-(-3))=>-5+3  ==>-2
0